The Higgs hunter's guide (Perseus Publishing, 1990)
The Higgs Hunter's Guide is a definitive and comprehensive guide to the physics of Higgs bosons. In particular, it discusses the extended Higgs sectors required by those recent theoretical approaches that go beyond the Standard Model, including supersymmetry and superstring-inspired models.